The Urgency of a Minimum Debt Threshold as a Requirement for Bankruptcy Petitions: A Comparative Study of Minimum Debt Regulations in United States Bankruptcy Law: Urgensi Minimal Utang Sebagai Persyaratan Permohonan Pailit (Perbandingan Pengaturan Minimal Utang dengan Hukum Kepailitan Amerika Serikat) - Rana Syahla; Dimas Mahardhika Satriawan; Syahrul Kurniawan (Lex Renaissance, 2024)
This research aims to analyze the urgency of setting a minimum amount of debt as a requirement in bankruptcy applications in Indonesia by comparing it with the minimum amount of debt regulation in the United States. This type of research is normative legal research. The results of this research conclude that there is an urgency to regulate further bankruptcy requirements because the consequences of bankruptcy are very large for debtors, and Supreme Court Regulation Number 14 of 2019 concerning Procedures for Settlement of Simple Claims can be used as a reference in regulating the minimum amount of debt in the bankruptcy and the regulation of bankruptcy law in the United States, the US Bankruptcy Code is more comprehensive and responsive because it regulates the minimum amount of debt which is adjusted to the type of debtor who is going to file for bankruptcy. In contrast, Indonesia does not restrict the minimum amount of debt.Keywords: the minimum amount of debt, bankruptcy requirements, debtor AbstrakPenelitian ini bertujuan untuk menganalisis urgensi pengaturan minimal utang sebagai persyaratan dalam permohonan pailit di Indonesia dengan melakukan perbandingan dengan pengaturan minimal utang di Amerika Serikat. Jenis Penelitian ini merupakan penelitian hukum normatif. Hasil penelitian menyimpulkan bahwa adanya urgensi untuk mengatur syarat kepailitan lebih lanjut karena akibat pailit yang sangat besar bagi debitor dan Peraturan Mahkamah Agung Nomor 14 Tahun 2019 tentang Tata Cara Penyelesaian Gugatan Sederhana dapat dijadikan sebagai acuan dalam mengatur jumlah minimal utang dalam kepailitan dan pengaturan hukum kepailitan di Amerika Serikat dalam US Bankruptcy Code lebih komprehensif dan responsif karena memiliki pengaturan jumlah minimal utang yang disesuaikan dengan jenis debitor yang akan dimohonkan pailit, sedangkan Indonesia tidak mengatur jumlah minimal utang.Kata Kunci: jumlah minimal utang, syarat kepailitan, debitor.